1989
DOI: 10.1093/oxfordjournals.aje.a115310
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Retrospective Questionnaire Assessing Diet 10–15 Years Ago

Abstract: In 1985, 216 men, participants in the Baltimore Longitudinal Study of Aging, were asked to report on their usual diet during the period 1971-1975. The reference data for past diet consisted of multiple seven-day records collected between 1971 and 1975. The group was randomly assigned to complete the diet history either by personal interview or by mailed self-administered questionnaire. The items and response categories were identical in both cases. For both groups, the mean nutrient intake estimated by questio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
1
3

Year Published

1992
1992
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 140 publications
(57 citation statements)
references
References 0 publications
2
51
1
3
Order By: Relevance
“…Block and Hartman (1989) have pointed out that age appears to have little adverse affect on the validity of questionnaires, at least when administered by interview, which is in concordance with the impression in this study. Different authors have found a good correlation to reference data among older respondents (Cummings et al, 1987;Sobell et al 1989;Brown, Fisher and Johnson, 1993), and better response rates among elderly than younger subjects have also been found (Jørgensen et al, 1993). A tendency to over reporting of 'desirable' food items such as fruit, bread and potatoes has been reported (Pietinen et al, 1988;Nes et al, 1992).…”
Section: Design and Quality Of The Dietary Assessment Instrumentmentioning
confidence: 91%
“…Block and Hartman (1989) have pointed out that age appears to have little adverse affect on the validity of questionnaires, at least when administered by interview, which is in concordance with the impression in this study. Different authors have found a good correlation to reference data among older respondents (Cummings et al, 1987;Sobell et al 1989;Brown, Fisher and Johnson, 1993), and better response rates among elderly than younger subjects have also been found (Jørgensen et al, 1993). A tendency to over reporting of 'desirable' food items such as fruit, bread and potatoes has been reported (Pietinen et al, 1988;Nes et al, 1992).…”
Section: Design and Quality Of The Dietary Assessment Instrumentmentioning
confidence: 91%
“…The questionnaire has excellent reliability and has been validated against multiple 4-day and 7-day food records. [26][27] Dietary Adherence-At each assessment point, participants were asked, "How well are you following the diet plan given to you by the dietitian?" They responded on a 9-point Likert scale that ranged from 1 ("not well at all") to 9 ("very well").…”
Section: Methodsmentioning
confidence: 99%
“…This questionnaire has been validated in many different populations. [10][11][12][13][14] Energy and macronutrient content of the diet were calculated from the questionnaire. Dietary variety was calculated for seven main food groups: (1) low-fat bread, cereal, rice, and pasta (LFB); (2) fruits; (3) low-fat vegetables (LFV); (4) low-fat meat, poultry, fish, dry beans, eggs, and nuts (LFM); (5) high-fat foods from the five main groups of the FGP (HFF); 7 (6) fats, oils, and sweets (FOS); and (7) combination foods.…”
Section: Methodsmentioning
confidence: 99%